Cultivating well-being beyond symptomatology in a clinical sample with paranoid tendencies; the feasibility, acceptability and possible benefit of a group intervention. Issue 4 (3rd July 2020) - Valiente, Carmen; Espinosa, Regina; Contreras, Alba; Trucharte, Almudena; Duque, Almudena; Nieto, Juan; Lozano, Belen; Chaves, Covadonga
ABSTRACT: The promotion of well-being is essential in the recovery process of mental health problems and has been shown to predict remission in psychosis. Even for severe mental illness where there has been and pessimistic view of prognosis, there is an increased awareness in the need for a positive movement, focusing on well-being and positive psychosocial factors in its treatment. The aim of this study is to provide data on the feasibility and acceptability of a manualised group intervention to improve well-being in a sample of patients with paranoid tendencies. Results showed that the protocol was feasible and highly acceptable for participants, showing high attendance and adherence as well as high satisfaction. On completion of group therapy, participants reported a significant improvement in different domains of well-being, with larger effects in self-acceptance and positive relationships with others. There was also significant improvement in self-esteem and significant decrease in paranoid ideation and anxiety. The results indicate that positive psychology group therapy may be a powerful complementary strategy in mental health promotion among people with paranoid tendencies. Though the validity of the study is limited by the lack of a comparison group, the present study will allow optimisation of a future RCTs.